Miracles : A Very Short Introduction - Nagasawa, Yujin (Great Clarendon Oxford University Press, 2017)
"Jesus turned water into wine, Mohammad split the moon into two, and Buddha walked and spoke immediately upon birth. According to recent statistics, even in the present age of advanced science and technology, most people believe in miracles. In fact, newspapers and television regularly report alleged miracles, such as recoveries from incurable diseases, extremely unlikely coincidences, and religious signs and messages on unexpected objects. In this book the award-winning author and philosopher Yujin Nagasawa addresses some of our most fundamental questions concerning miracles. What exactly is a miracle? What types of miracles are believed in the world's great religions? What do recent scientific findings tell us about miracles? Can we rationally believe that miracles have really taken place? Can there be acts that are more religiously significant than miracles? Drawing on a vast variety of fascinating examples from across the major religions, Nagasawa discusses the lively debate on miracles that ranges from reported miracles in ancient scriptures in the East and West to cutting-edge scientific research on belief formation."--Publisher information.
Include Illustrations and Index
Keywords: Miracles -- RELIGION / Comparative Religion